SOCIO-ECONOMIC NATURE AND IMPORTANCE OF INVESTMENT PROJECTS - Xurramov Zufar (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
In the article, studies revealing the essence of the investment project are divided into groups and modern approaches are summarized. Funding sources for investment projects are divided into groups. Investment projects are segmented based on their tasks and hierarchical levels are defined. A scientific conclusion and practical recommendations aimed at the implementation of investment projects have been developed.